Are interest rate caps a relevant tool to cool down overheating microfinance markets?. (8th July 2021) - Caballero‐Montes, Tristan; Godfroid, Cécile; Labie, Marc
Abstract: Interest rate caps may generate adverse effects for microfinance institutions and their clients. Interest rate caps imposed in competitive and highly saturated markets may favor the commercial mindset of microfinance institutions to the detriment of social outreach. In Cambodia, the recent interest rate cap has likely not contributed to protecting the poor, slowing down the market, or reducing the risk of over‐indebtedness. Policymakers and regulators should consider market conditions, especially the degree of competition when making regulatory decisions that may substantially affect the microfinance industry.